Research Trends and Geographical Contribution in the Field of Perinatal Mental Health: A Bibliometric Analysis from 1900 to 2020 - Usman Ali; Ahmed Waqas; Muhammad Ayub (Women's Health Reports, 2022)
Objective: The object of this research is to identify growth and geographical distribution of research in the field of perinatal mental health and key research areas. Materials and Methods: We performed a bibliometric analysis on research documents on perinatal mental health from 1900 to 2020. Web of Science was used to download bibliometric data. Search strategy used generic index terms with specific free text searches using ?AND? as Boolean function. For example, psycho AND perinatal. Microsoft Excel was used to identify research growth, geographical and research institutes contribution to research in the field. Citation analysis was done using VOSviewer. Results: A total of 11,081 articles were extracted. The most cited research was by Cox et al., which introduced Edinburgh Postnatal Depression Scale. There was exponential increase in the research documents from 1990 to 2020. However, most of the research was contributed by the global north. Among emerging countries, India, South Africa, and Brazil did not contribute in the perinatal research. Postnatal depression and its risk factors were most studied themes. Paternal perinatal mental health and impact on mental health of children were understudied themes. Conclusion: Perinatal mental health research outpaced growth in biomedical research in the past 30 years. The work of leading researcher in the field was initially inspired by his experience in Uganda encountering postnatal depression. However, even after half a century, there is still less contribution from developing countries. This analysis highlights research and possibly access to services inequities in developing countries.